Case Report of A Man Suffering From Bipolar Affective Disorder with Co-Morbid Obsessive Compulsive Disorder - Ali, Syed Azhar; Zubair, Usama Bin; Rana, Mowadat Hussain (Journal of Pakistan Psychiatric Society, 2018)
ABSTRACT